2021
DOI: 10.1002/jat.4166
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subacute inhalation toxicity assessment of WS‐23 in Sprague–Dawley rats

Abstract: 2‐isopropyl‐N,2,3‐trimethylbutyramide (WS‐23) is a well‐known artificial synthesis cooling agent widely used in foods, medicines, and tobaccos. As a commonly cooling agent in e‐cigarette liquids, WS‐23 has led to concerns about the inhalation toxicity with the prosperous of e‐cigarettes in recent years. Thus, the aim of this study is to assess the acute and subacute inhalation toxicity of WS‐23 in Sprague–Dawley (SD) rats according to the Organization for Economic Cooperation and Development (OECD) guidelines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Cellular genotoxic assays observed clastogenic effects of WS-23, inducing breaks in chromosomes on metabolic activation 53. A 4-week WS-23 rat inhalation toxicity study conducted by an e-cigarette company (RLX Technology, China) that administered 19 mg/kg body weight/day and 29 mg/kg body weight/day detected exposure-related changes for several lung function parameters 58. Across these studies, no-observed-adverse-effect levels for WS-23 and WS-3 were determined to be 5 mg/kg body weight/day and 8 mg/kg body weight/day, respectively.…”
Section: Chemistry Pharmacology and Toxicology Of Ice-hybrid Flavors ...mentioning
confidence: 99%
“…Cellular genotoxic assays observed clastogenic effects of WS-23, inducing breaks in chromosomes on metabolic activation 53. A 4-week WS-23 rat inhalation toxicity study conducted by an e-cigarette company (RLX Technology, China) that administered 19 mg/kg body weight/day and 29 mg/kg body weight/day detected exposure-related changes for several lung function parameters 58. Across these studies, no-observed-adverse-effect levels for WS-23 and WS-3 were determined to be 5 mg/kg body weight/day and 8 mg/kg body weight/day, respectively.…”
Section: Chemistry Pharmacology and Toxicology Of Ice-hybrid Flavors ...mentioning
confidence: 99%
“…Recently, an e-vapor product company (RLX technology, China) has conducted a nose-only acute and sub-acute inhalation study for WS-23 (28-day exposure at doses of 19 and 29 mg/kg-bw/day) 24 . Whole-body plethysmography was conducted after 28 days of repeated exposure to measure various parameters of pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of airway-epithelial cells in-vitro to various concentrations of synthetic coolants and WS-23 containing e-liquids also demonstrated a dose-dependent cellular toxicity 15 . A recent inhalation exposure study in rodents by an E-liquid manufacturer for WS-23 determined a NOAEL of 29 mg/kg-bw (342 mg/m3) in rodents 24 . Due to their evident toxicity and increased use in E-cigarettes, it is critical to evaluate the potential health risks associated with synthetic coolant exposure from E-cigarette use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent studies, rats exposed to aerosolized e-liquid containing WS-23 at tested doses (via acute and subacute exposures) found no substantial changes in histopathologic analyses of vital organs nor relative organ weights(Wu, Liu et al 2021). This same study, via a bronchioalveolar lavage fluid (BALF) analysis, found no significant difference in neutrophil concentration between rats which had undergone repeated 28-day WS-23 exposure and those apart of the respective control group(Wu, Liu et al 2021).Neutrophils are major sources of endogenous ROS production.Future studies aimed at understanding the role of WS-23 in modulating e-cig-induced oxidative stress should involve measurements of intracellular and extracellular ROS using isolated Polymorphonuclear Neutrophils (PMNs)(Kuhns, Priel et al 2015). More specifically, PMNs isolated from blood collected from mice exposed to aerosolized e-liquids of varying WS-23 concentrations can be analyzed via luminol enhanced chemiluminescence exposure(Kuhns, Priel et al 2015).…”
mentioning
confidence: 97%